The Investigation of Genetic Variation at Microsatellite Loci in Mazandaran Native Chickens - Nassiri, M.T. Beigi; Hamidi, Z.; Tavakoli, S. (International Journal of Poultry Science, 2007)
Blood samples of Mazandaran native chickens were collected. A total of 90 genomic DNAs were isolated through optimized and modified salting-out procedure. The samples were used in Polymerase Chain Reaction (PCR) with 20 micro satellite markers. Amplified PCR-products with the markers were separated on 8% denaturing polyacrylamide gel. One locus (MCW216) was monomorphic. According to allele frequencies of 20 micro satellite sites, mean heterozygosity (H) and Polymorphism Information Content (PIC) were calculated. The number of alleles varying from 1 to 6 and an estimate of average heterozygosity excluding the monomorphic data was calculated as 0.5872. The average heterozygosity and PIC value calculated from data on polymorphic and monomorphic loci was 0.5579 and 0.4939, respectively. The results of the heterozygosity were consistent with that of PIC. Diversity estimates in this study are lower than the observed frequencies of heterozygotes reported in other species using micro satellite markers. Other parameters for intrapopulation variation and Hardy-Weinberg proportions were also considered. All the loci except MCW222 and MCW165 showed deviations from Hardy-Weinberg equilibrium (p<0.005). Some of micro satellite sites were highly polymorphic, so they were effective markers for genetic diversity analysis. These results could provide basic molecular data for the research on the germplasm characteristics of Mazandaran native chickens.